2003
DOI: 10.1002/elps.200305553
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution single‐stranded DNA analysis on 4.5 cm plastic electrophoretic microchannels

Abstract: Plastic microchannels (4.5 cm long) fabricated from an etched glass master were tested for high-resolution single-stranded DNA analysis. Using replaceable denaturing linear polyacrylamide as sieving matrix, one-color separation of a fragment sizing standard with single-base resolution (R > 0.5) was achieved up to 275 bases. Two-color sizing analysis of four loci short tandem repeat (STR) allelic ladder (CSF1PO, TPOX, TH01, vWA) with single-base resolution (R = 0.62) on TH01 alleles 9.3 (198 bp) and 10 (199 bp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…Thus, the 4% pDMA matrix gives the best resolution of both smaller and larger fragments and is the best of the three sequencing matrices. Table 2 also reports sequencing times in these matrices, which are up to 66% lower than in any other chip sequencing report published (8,(18)(19)(20)(21)29). Because most microchip-based DNA sequencing studies have used longer channels as well as different electric field strengths and temperatures in efforts to optimize each individual system, it is difficult to compare migration times in our system directly with their published sequencing times.…”
Section: Dna Sequencing Resultsmentioning
confidence: 99%
“…Thus, the 4% pDMA matrix gives the best resolution of both smaller and larger fragments and is the best of the three sequencing matrices. Table 2 also reports sequencing times in these matrices, which are up to 66% lower than in any other chip sequencing report published (8,(18)(19)(20)(21)29). Because most microchip-based DNA sequencing studies have used longer channels as well as different electric field strengths and temperatures in efforts to optimize each individual system, it is difficult to compare migration times in our system directly with their published sequencing times.…”
Section: Dna Sequencing Resultsmentioning
confidence: 99%
“…Woolley and Mathies (1995) demonstrated the first application of DNA sequencing using a microfabricated glass device in 1995, reporting single-base resolution using their four-color scanner technology. Data quality and readlengths have improved significantly since then, because of an increase in the effective separation lengths with run times of 30 minutes or less (Table 2) (Woolley and Mathies 1995;Liu et al 1999;Schmalzing et al 1999;Backhouse et al 2000;Koutny et al 2000;Liu et al 2000;Salas-Solano et al 2000;Simpson et al 2000;Boone et al 2002;Paegel et al 2002;Shi and Anderson 2003). For example, Liu et al (1999) reported 99.4% accuracy over 500 bases in 20 minutes, with an increase in separation length from 3.5 cm to 6.5 cm.…”
Section: Microfluidic Separation Platformsmentioning
confidence: 99%
“…For example, Liu et al (1999) reported 99.4% accuracy over 500 bases in 20 minutes, with an increase in separation length from 3.5 cm to 6.5 cm. More recent developments by Boone et al (2002) and Shi and Anderson (2003) have shown the first DNA sequencing applications on plastic chips (Table 2). These chips can be fabricated with high geometric aspect ratios (i.e., deep and narrow channels) at significantly lower cost.…”
Section: Microfluidic Separation Platformsmentioning
confidence: 99%
“…Recently, Shi and Anderson [35] have reported the use of a polymeric microdevice for the separation of ssDNA fragments and successfully achieved single basepair resolution using a polyolefin device coated with poly-DMA/ diethylacrylamide. The authors attributed their ability to achieve single base resolution primarily to their matrix selection, a 4% w/v of 5.5 MDa linear polyarcylamides (LPAs); however, they did not investigate the significance of their coating material and whether the same resolution was achievable using the native polyolefin.…”
Section: Introductionmentioning
confidence: 99%